Case Report: Retroperitoneal Sarcoma in Six Operations: Our Experience in Operative Management of Blood Vessels - Guo, Jinhui; Qiu, Fabo; Zhao, Jie; Lu, Qiliang; Fu, Wen; Xu, Qiuran; Huang, Dongsheng (Frontiers in Oncology, 2022)
Here we introduce a case of retroperitoneal liposarcoma, which is characterized by repeated recurrences after surgery, and has undergone a total of 6 operations. The diameter of the tumor was about 26 cm at the time of the patient's diagnosis. The imaging examination revealed that the surrounding organs and blood vessels were invaded, which brought great challenges to radical resection. The postoperative pathology of the patient’s first operation was dedifferentiated liposarcoma, and some areas showed myxofibrosarcoma differentiation. With the recurrence of sarcoma, myxofibrosarcoma dedifferentiated into rhabdomyosarcoma, and malignant fibrous histiocytoma appeared in some areas. How to treat this type of patient after recurrence? How to deal with blood vessels wrapped by sarcoma during surgery? The medical community has not yet reached the same conclusion. We describe the process of treating the patient and the experience of dealing with blood vessels during surgery.